The Influence Of Letters Of Meanings In Determining The Meaning: An Applied Study of the Verses' Interpretation of the Determining the Fetus Gender Timing in Contemporary Exegeses/ أثر حروف المعاني في توجيه المعنى - دراسة تطبيقية في تفسير آيات توقيت تحديد جنس الجنين في التفاسير المعاصرة - Ahmad S Burhan; Abdulaziz E Hajji; Ali M Asaad; Fehmieh R Nawaya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Teaching the use of letters of meanings is an essential part of teaching the Arabic language, as these letters affect the meaning of speech, and their grammatical and semantic functions are synergistic to determine the meanings. The research aims to clarify the effects of the letters of meanings in determining the meaning by conducting an applied study on the verses that talk about the timing of determining the gender of the fetus in the Holy Qur’an. This topic was chosen for the presence of three verses that talk about it, each containing one of the letters of meaning. Thus, by studying the interpretations said, it is possible to determine the impact of the presence of these tools in the verses on determining their meanings. A complete extrapolation included what was mentioned in the most critical contemporary interpretations of the Holy Qur’an about the interpretation of the verses under study. Since this applied study deals with a topic of empirical science, it was helpful to cite the most important scientific references related to this topic. Both analytical and critical methods were assumed. The results proved the significance of the letters of meanings in determining the meanings and that they are indispensable in text understanding. It seems by specifying the semantics of (if) in the two verses of Surat An-Najm that they talk about the timing of determining the chromosomal sex of the fetus that occurs when the sperm fertilization occurs, while the letters (afterwhile and then) in the verses of Surat Fatir and Surat Qiyamah indicate that the verses talk about the timing of determining the organic sex of the fetus represented by the formation of genitals. By reviewing the textbooks of embryology and obstetrics, it was possible to clarify the accuracy of the meanings given by these letters. It is recommended to give the letters of meanings more attention during the educational process because of their widespread use in the Arabic tongue and their significant impact on the meanings that speech carries and performs